2011
DOI: 10.1007/s12028-011-9634-4
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Infarction in Adults with Bacterial Meningitis

Abstract: Cerebral infarction is a common and severe complication in adults with community-acquired bacterial meningitis. Preventing cerebral infarctions will be important in reducing the high morbidity and mortality rate in adults with community-acquired bacterial meningitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
72
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(77 citation statements)
references
References 31 publications
4
72
0
1
Order By: Relevance
“…For endocarditis and meningitis, AMI and AIS risk estimates in our study were particularly high but were less than the ≥10% reported in previous studies that included hemorrhagic stroke outcomes. 20,21 Most previous cohort studies on the association between infection and cardiovascular events lacked a comparison group or did not have adequate long-term follow-up. One small cohort study compared 208 patients hospitalized for pneumonia with 395 hospitalized controls and found an 8-fold risk increase for acute coronary syndrome within 15 days, 9 higher than our 2.2-fold increased RR within 30 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For endocarditis and meningitis, AMI and AIS risk estimates in our study were particularly high but were less than the ≥10% reported in previous studies that included hemorrhagic stroke outcomes. 20,21 Most previous cohort studies on the association between infection and cardiovascular events lacked a comparison group or did not have adequate long-term follow-up. One small cohort study compared 208 patients hospitalized for pneumonia with 395 hospitalized controls and found an 8-fold risk increase for acute coronary syndrome within 15 days, 9 higher than our 2.2-fold increased RR within 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…Cohort studies have reported short-term risks of AMI and stroke varying from 0.2% to >10% after patients have been hospitalized with pneumonia, sepsis, endocarditis, or meningitis. [7][8][9][10][11][19][20][21] …”
mentioning
confidence: 99%
“…In a previous study, we showed that cerebral infarction was present in 25% of 696 patients with bacterial meningitis. 18 Ischemic stroke is also a major complication in endocarditis patients; in a previous cohort study of 1437 patients, 15.2% developed cerebral infarctions. 19 In patients with both bacterial meningitis and endocarditis, there seems to be an additional risk at developing ischemic stroke; 9 of 24 patients (38%) with both bacterial meningitis and endocarditis developed cerebral infarctions in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A cerebral infarction is a severe complication of bacterial meningitis, reported as a result of vasculitis, vasospasm, endocarditis, or intra-arterial thrombosis. Only a few cohort studies on cerebral infarctions in bacterial meningitis have been published (5)(6)(7)(8). Cerebrovascular involvement, including cerebral infarction, is particularly common in pneumococcal meningitis (5, 9, 10) and typically occurs only in the acute phase of bacterial meningitis (11).…”
Section: Discussionmentioning
confidence: 99%